Wincenty Lutosławski i polski wkład w światowe badania nad Platonem - Paczkowski, Przemysław (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
Przedmiotem analizy są historyczno-filozoficzne dokonania Wincentego Lutosławskiego. Polski uczony zajął trwałe miejsce w światowych badaniach nad Platonem, ostatecznie rozstrzygając słynną „kwestię Platońską”, czyli problem chronologii dialogów. W rezultacie stylometria bywa do dziś – i słusznie – określana jako „polski wkład” w te badania.

This article examines the historical and philosophical achievements of Wincenty Lutoslawski. Polish scholar occupied a lasting place in the global studies on Plato, had eventually resolving the famous "Platonic question", that is, the problem of chronology of the dialogues. As a result, the stylometry is today – and rightly so – referred to as the "Polish contribution" to these studies.
Keywords: stylometria; Platon; Lutosławski Wincenty